PENGARUH E-SERVICE QUALITY TERHADAP KESETIAAN PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PERUSAHAAN PENERBANGAN PT. GARUDA INDONESIA - Azwar, Azwar; Sulaiman, Sulaiman (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
Researh’s aims is to determine the effect of service quality on customer satisfaction  and its subsequently on customer loyalty of PT. Garuda Indonesia. Data analysis uses the SPSS application version 22. Based on the results of research on 100 respondents with purposive sampling methods that E-Service Quality positively .and significantly affect customer satisfaction, E-Service Quality positively .and significantly affects Customer Loyalty. Futhermore, E-Service Quality indirectly impacts positively and significantly on Customer Loyalty mediated by Customer Satisfaction. Implication of this study is to gather more customer loyalty; the company needs to consider e-service quality in order to increase its customer satisfaction.